Pengaruh Pendidikan Praktek Kewirausahaan Dan Ekspektasi Pendapatan Terhadap Minat Berwirausaha Mahasiswa - Ari Ani Dyah Setyoningrum (PPPM Polimarin, 2022)
The COVID-19 pandemic provides very valuable learning, especially for students to make breakthroughs in entrepreneurship. Entrepreneurship provides opportunities for students to earn income. With entrepreneurship, the opportunity to earn a large income is wide open than being an employee. Expectations or hopes for a better income are one of the factors that influence whether a person wants to become an entrepreneur or not (Afrizal, Rafiy, & Nusantara, 2018). In addition, entrepreneurship practice education also affects students' interest in entrepreneurship. Entrepreneurial mental attitude in students can be instilled through entrepreneurship practice education based on entrepreneurial values ​​(Suryana, 2013). The purpose is to analyze the effect of income expectations and entrepreneurial practice education on students' interest in entrepreneurship. This research design uses quantitative research methods. Data collection techniques were carried out by interviews and questionnaires. The analytical technique used in this research is descriptive statistics. The analytical tool used is the SmartPLS version 3.0 software. The research prove that the variables of income expectations and entrepreneurial practice education have a significant positive effect on students' interest in entrepreneurship.